Challenges in establishing the professional ergonomist certification scheme in Malaysia - Mohd Tamrin, Shamsul Bahri; Syed Mohamed, Muhammad Syafiq; Ng, Yee Guan (Japan Ergonomics Society, 2017)
The certified professional ergonomist scheme is a requirement for any country that wishes to recognize the field of ergonomics as a professional service rendered by qualified and competent persons for the benefit of the public. Various countries like USA, Europe, Australia and New Zealand have already established the professional ergonomist scheme in their countries. However the recognition for the need to have a professional ergonomist certification scheme is slowly being brought forth in developing countries such as Malaysia, where the field of ergonomics is relatively unknown to the Malaysian public. However, since the field of ergonomics have become more popular in Malaysia, the need to have a Malaysian professional ergonomist certification scheme became quite important. Developing a professional ergonomist certification scheme in Malaysia is not without any challenges. Some of the notable challenges are the absence of any clearly stated standards or regulation within legal framework which requires ergonomics competency, establishing educational standards which are culturally relevant to Malaysia, establishing the route of certification which suites Malaysia context due to diversity of experience, exposure to ergonomics intervention and other programs and operational challenges in setting up Malaysian ergonomist certification framework. All these challenges are described in this paper.